A New Reformed Catholicity: Catholicity and Confessing in Reformed Ecclesiology - Kuo, Henry S. (Interreligious Studies and Intercultural Theology, 2019)
Reformed ecclesiology suffers from a lack of a concrete sense of catholicity, a lack that easily shatters unity in the church. This article broadly sketches a way in which Reformed confessions and the practice of confessing can help fill that lack, drawing from Robert Schreiter’s The New Catholicity. By understanding confessing in terms of re-membering dangerous memories, Reformed catholicity has the potential for enabling the church to be a unifying witness in an age where globalizing forces have fragmented societies and inflamed troubling sentiments.